Rangkaian Tradisi Neno Bo’ha Terhadap Kesehatan Ibu Melahirkan dan Bayi di Kabupaten Timor Tengah Selatan: Studi Literatur - Rahmawati, Windi Chusniah; Fikri, Aizatul; Ningrum, Fiyona Yulita; Rahmawati, Raida Ananda; Desandyansyah, Salmania Khnsa’ Nabila; Ilahi, Veny Autentica Rahma; Gunawan, Yuvica Novita (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
The Neno Bo'ha tradition is a tradition carried out for 40 days by mothers after giving birth. This tradition in East Nusa Tenggara has been proven to be one that influences the prevalence of the condition of mothers and toddlers. The Neno Bo'ha tradition carried out by mothers after giving birth tends to not pay attention to personal and baby hygiene and consumes high levels of carbohydrates but low levels of protein, thus having an impact on post partum cleanliness and sanitation around the baby. This tradition increases the high number of infections or malaria in East Nusa Tenggara, which according to the Central Statistics Agency is already high. This qualitative research using the literature study method was carried out with the aim of finding more incidents of the impact of this tradition so as to obtain results of the urgency of replacing the Neno Bo'ha tradition on the health and hygiene of postnatal mothers and babies. Solutions that can be implemented include approaching community leaders, providing education to local communities, involving local health workers to work together, both in education and treatment, and creating replacement innovations without eliminating the basic values ​​of these traditions.